Use Of Sugarcane Biomass In Brazil - LUCENA, Juliana de Almeida Yanaguizawa; SILVA, Letícia Matias Batista da (International Journal of Environmental, Sustainability, and Social Science, 2021)
Recently, the use of biomass energy has been growing worldwide on an accelerated trajectory, with the prospect of staying among the main renewable energy sources for the coming decades, along with wind and solar energy. Brazil is the largest producer of sugarcane on the planet and the second-largest producer of ethanol. But in addition to sugar, first-generation ethanol, and vinasse (for ferti-irrigation), other by-products and process residues from the plants (such as bagasse, filter cake, vinasse, straw, and sugarcane tip) can be used for the production of thermal and electric energies and also second-generation ethanol and biogas fuels. In this context, this paper presents the current scenario of sugarcane biomass in Brazil, discussing issues involving the use of sugar-alcohol by-products for bioenergy and biofuel production. Furthermore, a study on the reuse of sugarcane bagasse fibers for the production of eco-composite material is also presented. Finally, the concepts of biomass energy are described from a bibliographic survey and the previous experiences of the authors.